Orientalist Critiques of Quranic Authenticity: A Critical Analysis of Abraham Geiger and Theodore Nöldeke - Sari, Imel Yulia; Hasibuan, Badoar; Hanton, Hanton (El-Rusyd, 2026)
Orientalist studies of the Quran have given rise to various criticisms that question the authenticity and originality of the revelation, one of which is the allegation that the Quran’s language is derived from Jewish traditions and earlier religions. Abraham Geiger and Theodore Nöldeke were Orientalist scholars who argued that certain vocabulary, religious concepts, laws, and stories in the Quran are closely linked to Jewish traditions and other foreign languages. This study aims to analyze Geiger and Nöldeke’s views on the allegations of linguistic duplication in the Quran and to examine Muslim scholars’ responses to these views. The study employs a qualitative method using a content analysis approach. Data were obtained from primary sources the works of Orientalists and secondary sources, including books, journals, and relevant literature on the sciences of the Quran (ulumul Quran). Data analysis was conducted using content analysis and descriptive-critical analysis. The results of the study indicate that the allegations of linguistic duplication in the Quran stem from a historical-philological approach that highlights similarities in vocabulary and traditions between the Quran and Jewish and Christian texts. However, Muslim scholars argue that these similarities are part of a process of acculturation and Arabization of language that does not diminish the authenticity of the Quran as a revelation from Allah. Thus, the existence of vocabulary that bears similarities to other languages cannot be used as a basis for denying the originality and miraculous nature of the Quran.